Social Networking for Language Education
XV, 237 p.
Keywords: Social networking is now one of the ways in which anyone can set out to learn or improve their language skills. This collection brings together different sets of learning experiences and shows that success depends on the wider environment of the learner, the kind of activity the learner engages in and the type of learning priorities he or she has.